Igneous Rock Associations 11. The Geology and Petrology of Seafloor Volcanic Rocks of the Northeastern Pacific Ocean, Offshore Canada - Cousens, Brian (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2010)
SUMMARY The seafloor within Canada’s Exclusive Economic Zone in the northeastern Pacific Ocean features examples of three kinds of volcanic activity: mid-ocean ridge, near-ridge seamount, and intraplate seamount volcanism. Volcanism on the northern Juan de Fuca and Explorer ridges, at inter-transform pull-apart rifts, and at near-ridge seamounts close to the Juan de Fuca and Explorer ridges, produces lavas with unusually variable geochemical compositions. Lavas incorporate variable contributions from both trace-element-depleted upper mantle and trace-element-enriched veins, blobs or streaks embedded in the depleted upper mantle. The latter may have originated as dispersed parts of ancient mantle plumes similar to a modern plume responsible for the formation of the intraplate Bowie Seamount.